Analysis of the implementation and implications of the regional government information system (SIPD) in regional financial management (Study in North Sulawesi Province) - Nangoy, Nikita Angelita Maria; Tinangon, Jantje J.; Warongan, Jessy D. L (Yayasan Widyantara Nawasena Raharja, 2025)
SIPD or Local Government Information System is an information system used in the North Sulawesi Provincial government as a regional development planning system, regional financial system, and local government system, including a local government guidance and supervision system. This study aims to determine the Implementation and Implications of SIPD in Regional Financial Management faced in relation to Permendagri 77 of 2020. The research method used is descriptive qualitative research using a case study approach. Based on the results of research conducted at BKAD North Sulawesi Province, Disdukcapilkb North Sulawesi Province and KIPS North Sulawesi Province, it has not been fully implemented optimally in accordance with Permendagri Number 77 of 2020. The results of this study are first, the implementation of expenditure in terms of payment for goods and services using the UP, GU and TU mechanisms is currently carried out by the Expenditure Treasurer /Assistant Expenditure Treasurer. Second, it is known that in one NPD there is only one provider of goods and services. Third, there are obstacles in the form of SIPD servers that often have problems with the network. Furthermore, the implications of SIPD in Regional Financial Management in North Sulawesi Province are influenced by applicable regulations, as well as facilitating human resources, reducing the use of paper (paperless) and helping to decide on policies that are fast and precise in decision making.